Intravenous ibutilide versus intravenous amiodarone for post-operative management of atrial fibrillation following coronary artery bypass grafting: a prospective randomized controlled double blinded trial - Gandhi, Ankur; Verma, Aradhaya; Sharma, Aditya; Gandhi, Sanjay; Salman, Mohammed Abdul; Singh, Deependra (International Journal of Research in Medical Sciences, 2021)
Background: Increased incidence of post-operative atrial fibrillation (POAF) is responsible for more post-operative complications, length of hospital stay and subsequent higher costs of hospitalization. This study was done to compare the efficacy and safety of ibutilide versus amiodarone for treatment of POAF following coronary artery bypass grafting (CABG). Methods: In this prospective, randomized, double blind controlled study, 60 patients posted for CABG developing POAF, divided randomly into 30 patients each in groups A and group I. Group A received IV amiodarone at 3 mg/kg over 20 minutes and group I received IV ibutilide at 0.01 mg/kg over 10 minutes (weight <60 kg) or 1 mg over 10 minutes (weight >60 kg). Patients underwent standard anesthetic technique and monitoring for CABG. All the demographic data, hemodynamic data were recorded in a structured manner. Results: Ibutilide showed significantly faster resolution of AF at 12.47±5.3 versus 22.9±7.68 minutes by amiodarone (p=0.000). Ibutilide was found to have significantly higher incidences of recurrence at 23.3% versus 0% by amiodarone (p=0.0048). Ibutilide showed significantly lesser hypotension 0% versus 26.67% with amiodarone (p=0.002). Conclusions: This study concluded that ibutilide was found to be better suited to treat POAF patients, who underwent CABG; due to its early and efficient resolution and reduced risk of hypotension.